2005
DOI: 10.1107/s1744309105032999
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, purification, crystallization and preliminary X-ray diffraction analysis of the VP8* carbohydrate-binding protein of the human rotavirus strain Wa

Abstract: Rotaviruses exhibit host-specificity and the first crystallographic information on a rotavirus strain that infects humans is reported here. Recognition and attachment to host cells, leading to invasion and infection, is critically linked to the function of the outer capsid spike protein of the rotavirus particle. In some strains the VP8* component of the spike protein is implicated in recognition and binding of sialic-acid-containing cell-surface carbohydrates, thereby enabling infection by the virus. The clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…The significant hydrogen-bonding scheme in which the arginine residues participate suggests that it would be unlikely for this to occur, though cannot be completely eliminated based on this crystal structure of Wa, since a symmetry-related molecule is packed directly above this region. Strongly supportive of their determined orientation being prevalent is that in both our Wa VP8* structures solved in a different crystal form (initial data published) 24 where this region is solvent exposed, and also in the human rotavirus strain DS-1 VP8* structure 17 a similar arrangement of the arginine residues straddling the cleft and secured by hydrogen bonds with the opposing β-strand occurs. This cleft appears nonoptimal for binding sialic acids and neither our structures from two different crystal forms of Wa VP8* both crystallised in the presence of Neu5Ac-α2Me, nor our STD NMR analysis of this ligand with the Wa VP8* (unpublished results) provide any evidence for Wa VP8* binding this particular sialic acid derivative.…”
Section: Human Rotavirus Strain Wa Vp8* 64-223 Crystal Structuresupporting
confidence: 53%
See 2 more Smart Citations
“…The significant hydrogen-bonding scheme in which the arginine residues participate suggests that it would be unlikely for this to occur, though cannot be completely eliminated based on this crystal structure of Wa, since a symmetry-related molecule is packed directly above this region. Strongly supportive of their determined orientation being prevalent is that in both our Wa VP8* structures solved in a different crystal form (initial data published) 24 where this region is solvent exposed, and also in the human rotavirus strain DS-1 VP8* structure 17 a similar arrangement of the arginine residues straddling the cleft and secured by hydrogen bonds with the opposing β-strand occurs. This cleft appears nonoptimal for binding sialic acids and neither our structures from two different crystal forms of Wa VP8* both crystallised in the presence of Neu5Ac-α2Me, nor our STD NMR analysis of this ligand with the Wa VP8* (unpublished results) provide any evidence for Wa VP8* binding this particular sialic acid derivative.…”
Section: Human Rotavirus Strain Wa Vp8* 64-223 Crystal Structuresupporting
confidence: 53%
“…X-ray crystal structure determination of CRW-8 VP8* 64-224 and Wa VP8* 64-223 in respective space groups P2 1 2 1 2 1 and P3 2 21 were done via molecular replacement. 24,26 We report here refinement (REFMAC 28 ) and analysis of these structures. Solvent-flattening and noncrystallographic symmetry averaging (implemented in CCP4 29 ) was done as appropriate.…”
Section: X-ray Crystallographic Structure Determination and Refinementmentioning
confidence: 97%
See 1 more Smart Citation
“…However, commonly used bacterial and viral sialidases remove only terminal sialic acids from sialylglycoconjugates. Sialic acid recognition by sialidasesensitive animal rotaviruses via VP8* is structurally well characterized through a series of crystallographic studies 13,[15][16][17][18][19][20][21] . Our recent studies using nuclear magnetic resonance (NMR) spectroscopy and cell-based assays identified GM1 as a ganglioside receptor for the human rotavirus strains Wa (P [8]) and RV-3 (P [6]), and revealed that the internal Nacetylneuraminic acid (sialic acid) residue of GM1 plays a key role in VP8* recognition 12,22 .…”
mentioning
confidence: 99%
“…The wild-type CRW-8 VP8* containing Pro rather than Ser at position 157 was produced (38). The Wa VP8* core (aa 64 to 223) was expressed as described before (59). RV-3 VP8*64-223 was cloned, expressed, and purified as described for the Wa VP8* core.…”
Section: Methodsmentioning
confidence: 99%